การพัฒนาองค์ความรู้เพื่อเป็นแนวทางในการบริหารความเสี่ยงของ โครงการในงานด้านวิศวกรรมของธุรกิจปิโตรเลียมและปิโตรเคมี - กุสุมา ธงชัยเวชรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Most of the risk management of current projects in the case study company has been performed by only the experiences of the project manager. Therefore, all potential risks may not be identified and lead to severe impacts on the project or the organization. This research aims to develop a body of knowledge for project risk management of engineering works which can be an effective guideline by studing various body of knowledge related to the project risk management process and current operations in engineering works of the company. All knowledge has been integrated into the proposed body of knowledge which consists of three parts. The first part explains a risk definition and a project risk management theory. The second part presents the project risk management guideline in engineering works. The last one shows examples of the contingency and mitigation plan. After applying the body of knowledge in the current works, severe impacts have been reduced. The project risk management has set up with standard processes. Furthermore, this research approach can be applied to develop the body of knowledge for risk management in other works of the petroleum and petrochemical project.